2021
DOI: 10.21203/rs.3.rs-289653/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibacterial Activity and Mechanism of Plant Flavonoids to Gram-positive Bacteria Predicted from their Lipophilicities

Abstract: Antimicrobial resistance seriously threatened human health, and new antimicrobial agents are desperately needed. As one of the largest classes of plant secondary metabolite, flavonoids can be widely found in various parts of the plant, and their antibacterial activities have been increasingly paid attention to. Based on the physicochemical parameters and antibacterial activities of sixty-six flavonoids reported, two regression equations between their ACD⁄LogP or LogD7.40 and their minimum inhibitory concentrat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…18 Flavonoids have several antimicrobial actions, such as inhibiting synthase, which is involved in nucleic acid synthesis, respiratory chain and energy metabolism, cytoplasmic membrane function, and cell envelope synthesis. 19 The bioactive compounds of A. bilimbi seem to cooperate in producing an adequate antibacterial mechanism effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Flavonoids have several antimicrobial actions, such as inhibiting synthase, which is involved in nucleic acid synthesis, respiratory chain and energy metabolism, cytoplasmic membrane function, and cell envelope synthesis. 19 The bioactive compounds of A. bilimbi seem to cooperate in producing an adequate antibacterial mechanism effect.…”
Section: Discussionmentioning
confidence: 99%
“…20 A. bilimbi leaf extract also has antibacterial action with the MIC at 30% and the MBC at 35% against Enterococcus faecalis bacteria. 19…”
Section: Discussionmentioning
confidence: 99%
“…This review involves an investigation of 29 individual Rhododendron species and a comprehensive and simultaneous study of Rhododendron. In the study of antibacterial activity 72 , it was found that the study on gram-positive bacteria and its activity against gram-positive bacteria were significant, but no visible components were found for gramnegative bacteria. The highly effective substances mentioned in this review will continue to increase in value as pioneers in drug development.…”
Section: Prospects and Conclusionmentioning
confidence: 99%
“…Flavonoids not only help fend off infections and reinforce our immune system; however, their use significantly decreases the incidence of antibiotic resistance. 9 As a result, these compounds are now being largely being researched and successfully used as nutraceuticals. Previous researches have depicted that biocompatibility and bio-safety is also an important requirement of the materials used for medical and dental applications whether in case of the treatment of disease or any other invasive procedure.…”
Section: Introductionmentioning
confidence: 99%